Bougas Beauty / Nur Nabila Ismail - Ismail, Nur Nabila (2021)
At the end of the case study, I managed to get a lot of knowledge about businesses in the real world. I also get opportunity to analyse the business’s strength and weakness. From this case study also, I managed to identify the aspects that can be approved over time. I choose to study about Bougas Beauty which is one of the best face products Malaysia. In this case, I had identified the type of business that this company had. The type of business that this company use is partnership business. This is because this product was created with toleration between a husband and wife or we called as business partner. Bougas Beauty has been recognized by all people in Malaysia citizens. This is due to the insufficient of face products that offers variety selection of the products. Products that were offered by this store was face cleanser, face serum, face scrub and so on. Bougas Beauty celebrates beauty for all-being, men and women equally. Bougas Beauty believes in producing quality skin care products that tackles the concerns of Asian’s skin community. Bougas Beauty strives to break the judgement on local products and be alongside with international brands, gradually.